Identifying interactions between policy, accountability and outcomes for adaptation of urban roads. (November 2020) - Cañavera Herrera, Juan Sebastián; MacAskill, Kristen; Haigh, Stuart
Highlights: A conceptual framework to understand adaptation planning of urban roads is presented. The framework is called the Expanded Adaptation Action Cycles (EAAC) framework. An analysis of a case study of Bogotá, Colombia using the EAAC framework is presented. The practical utility of the EAAC framework as a diagnostic tool is demonstrated. Abstract: Several decision-making frameworks are available to foster climate adaptation of road infrastructure, but these focus mainly on the adaptation of national or regional roads. Urban road infrastructure is equally important for the efficient functioning of society and it is imperative to understand the peculiarities of adapting these types of roads, however, existing frameworks may not be appropriate for this purpose. This paper presents a conceptual framework called the "Expanded Adaptation Action Cycles" (EAAC) that conceptualizes in a simple, yet comprehensive manner the adaptation planning processes of urban road infrastructure. A case study of the decision-making processes for the development and maintenance of the road network of Bogotá, Colombia was conducted to demonstrate the practical utility of this framework as a diagnostic tool. Analysing the evidence collected using the EAAC framework indicates that the city is currently at the early stages of its adaptation planning and that the adaptation measures being considered suggest that, at most, the city is aiming to implement incremental adaptation. This demonstrates how the EAAC framework provides the ability to understand the relative position of a city's approach to adaptation planning within a wider spectrum of possibilities, providing insight into the potential impact of possible planning interventions.